A Case of Lacrimal Sac Septum Presenting With Dacryocystocele. Issue 1 (January 2018) - Siapno, Debrelle Lou P.; Woo, Kyung In; Kim, Yoon-Duck
Abstract : Lacrimal sac septum is a rare structural abnormality of the lacrimal system. A 15-year-old patient presented with epiphora and a mass inferior to the left medial canthal tendon. Dacryocystography and CT-dacryocystography revealed a dilated lacrimal sac with complete obstruction. A horizontal lacrimal sac septum was found in the mid-sac region during endoscopic dacryocystorhinostomy. Histopathologic examination of the septum revealed chronic inflammation with stratified columnar epithelial cell lining consistent with the lacrimal sac. Abstract : A case of lacrimal sac septum in a 15-year-old male with complaints of epiphora and medial canthal mass.